2020
DOI: 10.1016/j.fertnstert.2019.09.039
|View full text |Cite
|
Sign up to set email alerts
|

High antimüllerian hormone levels are associated with preterm delivery in patients with polycystic ovary syndrome

Abstract: Context: Antim€ ullerian hormone (AMH) levels are higher in patients with polycystic ovary syndrome (PCOS). Accumulating evidence indicates that AMH has an impact on the physiology of the female reproductive system. Objective: To investigate the association of AMH levels with the risk of preterm delivery in PCOS patients. Design: Retrospective cohort study. Setting: Academic fertility center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Furthermore, parameters reflecting the quantity of ovarian reserve including AFC, number of retrieved oocytes and transferable embryos do not reflect the quality of oocytes and embryos. Moreover, our results did not include pregnancy complications, while PCOS was reported to be associated with gestational diabetes, pregnancy-induced hypertension, and premature delivery (54,55).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, parameters reflecting the quantity of ovarian reserve including AFC, number of retrieved oocytes and transferable embryos do not reflect the quality of oocytes and embryos. Moreover, our results did not include pregnancy complications, while PCOS was reported to be associated with gestational diabetes, pregnancy-induced hypertension, and premature delivery (54,55).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, underlying inflammatory mediators associated with PCOS may also contribute to predisposition for preterm delivery. Additionally, a recent study showed that higher antimüllerian hormone (AMH) levels were a risk factor for preterm delivery in women with PCOS (21). This result may be explained by the higher AMH level observed in PCOS women during pregnancy was considered to have an impact on the endocrine system of the fetus and offspring (22).…”
Section: Discussionmentioning
confidence: 99%
“…And the presence of scientific evidences in the literature indicating that in pregnant diagnosed with PCOS had a higher preterm delivery rate, especially those whom had higher AMH levels, emboldened us to plan this research. (8)(9)(10) When PCOS patients are evaluated within themselves, the most frequently detected abnormality was Figure II which is classified as class VI in ASRM classification and is accepted as a variance of normal, not abnor-mality, in ESGE -ESHRE classification, named as arcuate. When the arcuate cavity is considered normal as in the ESGE -ESHRE classification, in terms of uterine cavity abnormalities, the statistically significant difference disappears between PCOS and control patients.…”
Section: Discussionmentioning
confidence: 99%